Enhancing Javanese Script Literacy Through SIDORAWA Multimedia: A Case Study at an Islamic Elementary School - Bhismo Aji Wibowo; Harun Joko Prayitno; Fitri Puji Rahmawati (STAI Hubbulwathan Duri, 2025)
Literacy in reading and writing Javanese script among elementary school students remains low, primarily due to unengaging learning media and limited student motivation. To address this issue, this study explores the implementation of SIDORAWA (Sinau Karo Dolanan Aksara Jawa), an interactive multimedia application designed to enhance Javanese script literacy. A qualitative case study was conducted at Aisyiyah Surya Ceria Islamic Elementary School involving 28 fourth-grade students. Data were collected through interviews, classroom observations, and documentation. The Miles and Huberman interactive model was used for data analysis, and data validity was ensured through triangulation of techniques and sources. Findings indicate that SIDORAWA effectively improved students’ ability to read and write Javanese script. The application integrates visual, auditory, and interactive elements—including animations, sound, and culturally nuanced games—that enhance engagement and comprehension. Students showed increased motivation, active participation, and improved literacy outcomes, with reading and writing proficiency rising significantly after implementation. SIDORAWA not only supports academic literacy but also fosters digital and cultural literacy by embedding local cultural elements into the learning process. Although the study demonstrates positive outcomes, its scope is limited to a single class and school. Broader implementation across different contexts and integration into blended learning environments is recommended. Additionally, ongoing support through teacher training, infrastructure, and feature development is essential for maximizing its educational impact.